2019
DOI: 10.1590/0102-33062018abb0100
|View full text |Cite
|
Sign up to set email alerts
|

Fungi associated with Copaifera oblongifolia (Fabaceae) seeds: occurrence and possible effects on seed germination

Abstract: Copaifera oblongifolia is a recurrent plant species in degraded areas yet there is little information about its seed biology and interactions with fungi. The aims of this study were to identify the fungal community (endophytic and nonendophytic) associated with C. oblongifolia seeds and to test the effects of these different fungal species on germination. In general, germination of C. oblongifolia seeds was high (about 85 %), initiating four days after sowing and continuing for a total of 20 days. External ase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…EFs found in the leaves of tropical pioneer plants are, in general, generalists and can negatively affect seed germination and seedling development (Kluger et al, 2008). Copaifera oblongifolia is a tropical shrub invader of habitats in the initial stage of succession and does not have EFs associated with its seeds (Fernandes et al, 2019). Therefore, the fungi found in the leaves of C. Oblongifolia example, the species D. helianthi, D. heveae, N. parvum, P. prosopidis and Phomopsis sp.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…EFs found in the leaves of tropical pioneer plants are, in general, generalists and can negatively affect seed germination and seedling development (Kluger et al, 2008). Copaifera oblongifolia is a tropical shrub invader of habitats in the initial stage of succession and does not have EFs associated with its seeds (Fernandes et al, 2019). Therefore, the fungi found in the leaves of C. Oblongifolia example, the species D. helianthi, D. heveae, N. parvum, P. prosopidis and Phomopsis sp.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that EFs can inhibit (Jiang et al, 2008;Meepagala et al, 2016;Mazarotto et al, 2019), stimulate (Tudzynski and Sharon, 2002;Gallery et al, 2007;Khan et al, 2017) or not affect (Fernandes et al, 2019) the seed germination of different plant species. Germination inhibition can occur through the production of phytoinhibitors (Meepagala et al, 2016;Khiralla et al, 2018) or simply through the degradation of seed reserves, causing starvation and death of the embryo (Dhingra et al, 2002;Fagundes et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations